Cancer Cell Metabolism: A Review - Bordoloi, Rajashree; Bhuyan, Shuvam; Das, Abhijit (Journal of Drug Delivery and Therapeutics, 2019)
It has been known for decades that cancer cells exhibit enhanced rates of Glucose uptake and glycolysis. Rapidly growing Tumor cells display remarkably different metabolic autonomy from the tissues which they are derived. Tumor cells alter their metabolism to support growth and proliferation. In this study, we have re-examined the metabolism in tumor cells and have made an attempt to bring together the major contributions made to this topic till date. This review in particular highlights the altered metabolism in the high energy demanding tumour cells, genetic changes that alter tumour cell metabolism and the role of metabolic microenvironments that may promote malignant progression.Keywords: Crabtree, Warburg, Metabolic microenvironments, Hypoxia, pH,